(untitled) (Malaysian Journal of Learning and Instruction, 2024)
Purpose – Due to the dynamic nature of schools, the Department of Education currently faces significant issues including low teaching quality, teacher shortages, absenteeism, poor school climate, lack of well-trained and motivated instructors, and instability. Total Quality Management (TQM) is often linked to the school environment, teacher satisfaction, and performance, playing a crucial role in improving the quality of education. This paper aims to identify how teacher job satisfaction and school climate influence the relationship between TQM and school performance. Methodology – A total of 346 teachers from Pakistan’s highperformance schools and low-performance schools, with diverse positions and wage scales, were chosen as participants in this study using stratified random sampling. Data was collected quantitatively using a survey inquiry and SPSS version 24 was utilized to analyze the data and answers the study questions. The mediation procedure was evaluated using the Sobel test. Findings – Findings showed that the TQM variable has the highest mean value (mean=4.87) compared to the other variables tested, namely job satisfaction, school performance and school climate. According to the study’s findings, TQM, job satisfaction, and school climate all have a favourable and significant direct influence on school performance. Additionally, school climate and job satisfaction variables were found to be partial mediators linking TQM and school performance. Significance – This study significantly enhances school quality management through a positive environment and capable human resources. The findings are also anticipated to encourage the Pakistan government to establish organizational management and educational leadership training courses to emphasise the significance of TQM and its most efficient use in the education sector.